2021
DOI: 10.1128/msystems.00613-21
|View full text |Cite
|
Sign up to set email alerts
|

The Future of (Soil) Microbiome Studies: Current Limitations, Integration, and Perspectives

Abstract: Microbes dominate the planet’s biodiversity in terms of species number and by driving essential Earth system functions such as the carbon cycle. Soils contain most of this microbial biodiversity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Agricultural management intensity is a major driver of soil microbiome community structure, with this influence having been observed at the plot ( Hartmann et al, 2014 ), regional ( Felipe-Lucia et al, 2020 ), continental ( Fox et al, 2021 ), and even global scale ( Leff et al, 2015 ). Soil microorganisms can, however, also exhibit temporal variation ( Hannula et al, 2019 ), and the importance of such temporal aspects into soil microbiome studies is being increasingly highlighted in the literature ( Geisen, 2021 ). Despite this, the extent of this influence on the structure of the soil microbial community in agricultural systems, as well as the stability of any differences in community structure between differently managed systems, remains poorly understood ( Dunn et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural management intensity is a major driver of soil microbiome community structure, with this influence having been observed at the plot ( Hartmann et al, 2014 ), regional ( Felipe-Lucia et al, 2020 ), continental ( Fox et al, 2021 ), and even global scale ( Leff et al, 2015 ). Soil microorganisms can, however, also exhibit temporal variation ( Hannula et al, 2019 ), and the importance of such temporal aspects into soil microbiome studies is being increasingly highlighted in the literature ( Geisen, 2021 ). Despite this, the extent of this influence on the structure of the soil microbial community in agricultural systems, as well as the stability of any differences in community structure between differently managed systems, remains poorly understood ( Dunn et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In line with the saying related to the health of the human skin ‘ The skin never forgets ’, protecting the soil as the Earth's thin skin and the biodiversity therein needs to be a top priority to protect global biodiversity. Soils are experiencing an increasing number and severity of anthropogenic stressors (FAO, ITPS, GSBI, SCBD, EC, 2020; Geisen, 2021), but represent the basis for human nutrition and health (Banerjee & van der Heijden, 2022; FAO, ITPS, GSBI, SCBD, EC, 2020; Wall et al, 2015), calling for immediate action to maintain these essential nature's contributions to people. This has been known for decades, but little has been done since then (‘ The nation that destroys its soil destroys itself ’, Franklin D. Roosevelt, 1937).…”
Section: Discussionmentioning
confidence: 99%
“…Such dynamics in real‐world ecosystems and their implications for ecosystem functioning are a major gap in our understanding (Bergmann et al, 2020; Williams & de Vries, 2020). In addition, interactions between soil organisms are continuously updated (Bahram et al, 2018b; Bradford, 2016; Geisen, 2021; Guo et al, 2022), again mostly using controlled experiments. Expanding this growing understanding to real‐world conditions, as well as understanding their context‐dependence and response to global change, will be fundamental for understanding and predicting the impacts of global change on ecosystem functioning, including climate feedbacks (Crowther et al, 2019; Guerra et al, 2021b).…”
Section: Frontiers In Soil Ecologymentioning
confidence: 99%
“…Despite finding numerous ways that we can apply the functionality of microbiomes, there are still several challenges that need to be addressed before we can move forward in developing their full potential. For instance, efforts in identifying these microorganisms through metagenomics may be a breakthrough but it might lead us in mixing the functional ones with the inactive ones due to them being recovered from the same diversity [52]. This creates a need for a more in-depth study which requires us to identify each individual microbiome accordingly based on their functionality(s).…”
mentioning
confidence: 99%
“…In this paper we had listed the history of microbiome, its recent advancement and two case studies which showed its current applications. By reviewing through what had been discussed, we IOP Publishing doi:10.1088/1755-1315/1103/1/012014 10 realised there are still plenty of potential improvements that can be explored in future research which had been mentioned by S. Geisen (2021) [52], and G. [59]. These challenges and potential advancements may create a great opportunity for us as researchers to develop better methods of applying soil microbiome to potentially identify more functional bioactive compounds in the future.…”
mentioning
confidence: 99%